Kajian Stilistika dalam Novel Hati Suhita Karya Khilma Anis - Mardliyah, Zubaidatul; Sutejo, Sutejo; Astuti, Cutiana Windri (STKIP PGRI Ponorogo Press, 2021)
In literature, language style is often viewed as the author’s language technique to express all ideas in literary works with make it distinctive. This study is aimed at describing the language style in novel Hati Suhita by Khilma Anis based on stylistic theory; a theory that discusses the style or language style in a literary work, both in spoken and written. The researcher used qualitative research method and designed as literature review. The words of the object under study are the results of the study in this study. Based on the results of the study, it can be concluded that the novel author uses (1) comparative language styles found in this study include: parable language style, personified language style, allegory language style, pleonamse language style, antithesis language style, and corrective language style. (2) Conflict language styles found in this study include: hyperbole language style, litotes language style, zeugma language style, paradox language style, and climax language style. (3) Linkage language styles found in this study include: polysindetone style, asindeton language style, metonymy language style, euphemism language style, antonomasia language style, parallelism language style, ellipsis language style, and alusi language style. (4) The repetitive language styles found in this study include: anapora language style, epistrofa language style, epizeukis language style, alliteration language style, and assonance language style.